The Means and the Difficulties Faced by Maternal and Child Health Nursing Students in Obtaining Scientific Information in Practical training - Khairi, suhad (Iraqi National Journal of Nursing Specialties, 2012)
Objective: The aim of this study is to determine the means and the difficulties faced by students ofnursing maternal and child health nursing / College of Nursing / University of Baghdad in obtaining scientificinformation in practical training.Methodology: A purposive sample of (100) Nursing college student - Maternal and Child Health NursingDepartment were selected. Data were collected through the use of the questionnaire form during theperiod from the November 2010 to April 2011. Descriptive statistical procedures were used to analyze thedata.Results: The results showed that the highest percentage of members of the study sample aged between(20-21 years), females are the most inhabitants of the city of Baghdad. Results of the study revealed thatmore than half of the study sample to get their information from each of the library and the Internet, andthat half the study samples prefer the Internet, and more than two thirds of the study sample is consideredmore accurate information books. The study results showed that the highest percentage (63%) of the studysample prefer the Internet is due mostly to ease and shorten the time from the student's point of view; halfof the students who used the Internet choose what an appropriate topic is and leave the rest. The studyresults showed that the highest percentage (67%) of the study sample had difficulties in the Internet, mostof their weakness and lack of knowledge and skill to the Internet and computer from their point of view,the bulk of the proportion (95%) of the study sample have difficulties in the use of books, including the lack109of copies and a few books on the topic that student want, so the majority of the sample depend oncolleague in accessing information from the Internet.Recommendations: Provision educational programs for nursing to develop learning-oriented and selfproblem-solvingskills especially on a database, integration of computer courses in the curriculum, trainingof librarians to provide information about libraries and library services with the progress of lessons in areliable and effective assessment of students in the efficiency of the computer with the provision offeedback for students.